A novel variant of SFTPA2 in a Han Chinese family with interstitial lung disease and lung cancer. Issue 1 (1st January 2021) - Liu, Lv; Liu, Yi-Jie; Guo, Ting; Luo, Hong
Abstract : Interstitial lung disease (ILD) presents as progressive scarring of lung tissue, which may affect respiratory function and restrict oxygen-exchange into the bloodstream, finally leading to dyspnea, dry cough and decreased quality of life. Increasing evidence indicates that genetic factors may be crucial in the development of ILD. At present, the main pathogenic genes of ILD include genes vital for surfactant metabolism and function and telomere biology associated genes. Mutations in both sets of genes may induce the apoptosis of alveolar epithelial cells and finally result in remodeling of the lung interstitium. In this study, one Han Chinese family with interstitial pneumonia and lung cancer was recruited. The proband was selected for whole exome sequencing analysis. After data filtering, only a novel mutation (c.404G > A /p.G135E) of SFTPA2 (NM_001098668) was identified. No other meaningful mutations were detected. The mutation co-segregated with the affected patients in the pedigree and was absent in the healthy controls. Bioinformatics analysis predicted that this variant is pathogenic and located in an evolutionarily conserved site of the SP-A2 protein. This study further expands the variant spectrum of the SFTPA2 gene and may be helpful in the genetic counseling of interstitial pneumonia and lung cancer patients.